A Cross-Sectional Exploration of Research Outcome Expectations: Motivators for Dietetics Research Involvement. Issue 2 (April 2016) - King, Carrie; Parrott, J. Scott; Hand, Rosa
Abstract : Research outcome expectations are the perceptions that research involvement is, or is not, personally valuable. This study compared the research outcome expectations of dietetics professionals with different levels of research experience. Three hundred fifty-five members of the Academy of Nutrition and Dietetics completed an online survey (preprofessional students: n = 33 [3.3%], Dietetics Practice–Based Research Network members: n = 152 [11.2%], dietetics researchers: n = 170 [20.5%]). Significant differences were found between study groups for research outcome expectation ( P < .01) and research involvement ( P < .01). The practice setting is the ideal place to build dietetics research outcomes expectations through a collaborative strategy developed at the team or department level.